2006
DOI: 10.1007/s00040-005-0859-0
|View full text |Cite
|
Sign up to set email alerts
|

Disease and colony establishment in the dampwood termite Zootermopsis angusticollis: survival and fitness consequences of infection in primary reproductives

Abstract: Pathogens have likely infl uenced life-history evolution in social insects because their nesting ecology and sociality can exacerbate the risk of disease transmission and place demands on the immune system that ultimately can impact colony survival and growth. The costs of the maintenance and induction of immune function may be particularly signifi cant in termites, which have a nitrogen-poor diet. We examined the effect of fungal exposure on survival and reproduction during colony foundation in the dampwood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 37 publications
(56 reference statements)
2
32
2
Order By: Relevance
“…90448) was used to experimentally infect termites. This fungus naturally occurs with termites (Zoberi 1995) and has been cultured from Z. angusticollis cadavers found in freshly collected field colonies during a post-collection quarantine period (Calleri et al 2005(Calleri et al , 2006. A detailed description of the preparation of Tween 80 conidia suspensions is given in Rosengaus et al (1998).…”
Section: Methodsmentioning
confidence: 99%
“…90448) was used to experimentally infect termites. This fungus naturally occurs with termites (Zoberi 1995) and has been cultured from Z. angusticollis cadavers found in freshly collected field colonies during a post-collection quarantine period (Calleri et al 2005(Calleri et al , 2006. A detailed description of the preparation of Tween 80 conidia suspensions is given in Rosengaus et al (1998).…”
Section: Methodsmentioning
confidence: 99%
“… References: 1, Dixon & Kindlmann (1999); 2, Denno et al (1985); 3, Kisimoto (1956); 4, Dixon et al (1993); 5: Ahlroth et al (1999); 6, Fjerdingstad et al (2007); 7, Yano & Takafuji (2002); 8, Xiao et al (2007); 9, Ostergard et al (2007); 10, Greig (1993); 11, Traveset (1991); 12, Zagt (1997); 13, Fedriani & Manzaneda (2005); 14, Grimm (1995); 15, Silva & Taberelli (2001); 16, Young & Lockley (1988); 17, Bell et al (2005); 18, Cummings et al 1993); 19, Deblok & Tanmaas (1977); 20, Lundquist et al (2004); 21, Oliver & Retiere (2006); 22, Craig (1997); 23, Vahl & Clausen (1980); 24, Cheung et al (2006); 25, Vander Wall & Longland (2004); 26, Allen & McAlister (2007); 27, Hiddink et al (2002); 28, Hiddink & Wolff (2002); 29, Pechenik (1999); 30, Aukema & Raffa (2004); 31, Korb & Linsenmair (2002); 32, Srygley (2004); 33, Galeotti & Inglisa (2001); 34, Amo et al (2007); 35, Bonnet et al (1999); 36, Hamann et al (2007); 37, Jessop et al (2004); 38, Pietrek et al (2009); 39, Winne & Hopkins (2006); 40, Smallwood et al (2009); 41, Real & Manosa (2001); 42, Massemin et al (1998); 43, Kenward et al (1999); 44, Solomon (2003); 45, Soulsbury et al (2008); 46, Adamo et al (2008); 47, Srygley et al (2009); 48, Adamo & Parsons (2006); 49, Calleri et al (2006); 50, Bennet & Marshall (2005); 51, Crawford (1992); 52, Epp & Lewis (1984); 53, McHenry & Patek (2004); 54, Wendt (2000); 55, Combes & Dudley (2009); 56, Berrigan (1991); 57, Hedenstrom et al (2001); 58, Srygley & Ellington (1999); 59, Kram (1996); 60, Kramer & McLaughlin (2001); 61, Berrigan & Lighton (1994); 62, Full & Tullis (1990); 63, Duncan & Crewe (1993)…”
Section: Organisation Of Dispersal Costsmentioning
confidence: 99%
“…These correlations are likely to be expressed between and within dispersal‐related phenotypic traits including morphological, physiological, behavioural and life‐history traits. Genetic trade‐offs between functional wings and insecticide resistance (Vasquez‐Castro et al , 2009) or disease resistance (Adamo & Parsons, 2006; Calleri et al , 2006) are examples of deferred survival costs. Investments in flight morphology for long‐distance movements reduces acceleration speed in butterflies, inducing a negative impact on male‐male interactions and subsequent territory‐holding ability (Berwaerts, Aerts & Van Dyck, 2006; Bonte & Van Dyck, 2009; Kemp, Wiklund & van Dyck, 2006).…”
Section: Life‐history Trade‐offs and Feedbacks Among Dispersal Phmentioning
confidence: 99%
“…Previous studies have shown that colony of origin is a significant and independent predictor of termite survival against disease and that colony foundation and oviposition rates are strongly affected by an immune challenge (Rosengaus & Traniello, 1993;Rosengaus et al, 2000;Calleri et al, 2006Calleri et al, , 2007. It may be that the abiotic environment directly affects termites: warmer temperatures and/or higher RH may stimulate the immune system, thus decreasing susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…A number of life-history traits as well as extraneous biotic factors have been shown to influence various aspects of insect immune systems including nutrition (Siva-Jothy & Thompson, 2002), mating and reproduction (Siva-Jothy et al, 1998;Hosken, 2001;McKean & Nunney, 2001;Ahmed et al, 2002;Kraaijeveld et al, 2002;Rolff & Siva-Jothy, 2002;Calleri et al, 2006Calleri et al, , 2007, gender (Kurtz et al, 2000;Kurtz & Sauer, 2001;Rolff, 2001;Siva-Jothy & Thompson, 2002;Zuk et al, 2004;Baer et al, 2005), age (Rheins & Karp, 1985;Rolff, 2001), predation (Joop & Rolff, 2004), parasitism (Joop & Rolff, 2004), density (reviewed in Wilson & Cotter, 2008), and sociality (Traniello et al, 2002;Cremer et al, 2007;Cotter & Kilner, 2010;Hamilton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%